Patient‐reported outcomes with the β3‐adrenoceptor agonist mirabegron in a phase III trial in patients with overactive bladder. Issue 8 (19th August 2015) - Khullar, Vik; Amarenco, Gerard; Angulo, Javier C.; Blauwet, Mary Beth; Nazir, Jameel; Odeyemi, Isaac A.; Hakimi, Zalmai
Abstract : Aims: To assess patient‐reported outcomes (PROs) in patients with overactive bladder (OAB) receiving the novel β3 ‐adrenoceptor agonist mirabegron. Methods: Data from a randomised, double‐blind, controlled phase III trial in 1, 987 patients aged ≥18 years with OAB symptoms for ≥3 months were analysed. Patients received placebo, mirabegron 50 or 100 mg/day, or tolterodine extended release (ER) 4 mg orally once daily for 12 weeks after a 2‐week placebo run‐in. Prespecified analysis of PROs (changes in OAB Questionnaire [OAB‐q], Patient Perception of Bladder Condition [PPBC], and Work Productivity and Activity Impairment: Specific Health Problem [WPAI‐SHP] instrument) in patients treated with mirabegron 50 mg/day, tolterodine ER 4 mg/day or placebo is reported. Post‐hoc analyses of OAB‐q, PPBC and the Treatment Satisfaction‐Visual Analogue Scale (TS‐VAS) in patients who were incontinent at baseline are also reported. Results: Significant improvements over placebo in OAB‐q coping and concern from baseline to final visit were observed with mirabegron 50 mg/day. No significant improvements in these parameters were observed with tolterodine ER 4 mg/day. Mirabegron 50 mg/day significantly increased the proportion of patients showing a PPBC improvement over placebo. Mirabegron 50 mg/day also produced greater improvements in WPAI‐SHP presenteeism and greater reductions in absenteeism and overall work impairment than placebo or tolterodine ER 4 mg/day. The impact of mirabegron 50 mg/day treatment on PROs in the incontinent population appears to be greater than that in the overall OAB population. Conclusions: At the approved dose of 50 mg/day, mirabegron significantly improves OAB patients' perception of disease and quality of life, independent of whether they are incontinent at baseline. Neurourol. Urodynam. 35:987–994, 2016 . © 2015 The Authors. Neurourology and Urodynamics published by Wiley Periodicals, Inc.